Pengaruh Keaktifan Mahasiswa dalam Organisasi dan Disiplin Belajar Terhadap Prestasi Belajar Mahasiswa STIA BNM Pariaman - Wijaya, Reni (Pustaka Galeri Mandiri, 2025)
This study aims to determine the effect of student activity in organizations and learning discipline both partially and simultaneously on the learning achievement of STIA BNM Pariaman students. This study is an associative study with a quantitative approach. The population in this study were students majoring in State Administration Science at the Bina Nusantara Mandiri Pariaman College of Administrative Sciences, class of 2022 and 2023. Sampling in this study used the proportionate stratified random sampling technique with a total of 54 respondents. Data collection techniques used online questionnaires and documentation. The data analysis technique used was multiple regression analysis. The results of the study showed that: (1) There is a positive and significant effect of student activity in organizations on student learning achievement. (2) There is a positive and significant effect of learning discipline on student learning achievement. (3) There is a significant effect of student activity in organizations and learning discipline simultaneously on the learning achievement of students majoring in State Administration Science at the Bina Nusantara Mandiri Pariaman College of Administrative Sciences.